Chemical Mimics of Aspartate‐Directed Proteases: Predictive and Strictly Specific Hydrolysis of a Globular Protein at Asp−X Sequence Promoted by Polyoxometalate Complexes Rationalized by a Combined Experimental and Theoretical Approach. Issue 63 (15th October 2019) - Ly, Hong Giang T.; Mihaylov, Tzvetan T.; Proost, Paul; Pierloot, Kristine; Harvey, Jeremy N.; Parac‐Vogt, Tatjana N.
Abstract: Creating efficient and residue‐directed artificial proteases is a challenging task due to the extreme inertness of the peptide bond, combined with the difficulty of achieving specific interactions between the catalysts and the protein side chains. Herein we report strictly site‐selective hydrolysis of a multi‐subunit globular protein, hemoglobin (Hb) from bovine blood, by a range of Zr IV ‐substituted polyoxometalates (Zr‐POMs) in mildly acidic and physiological pH solutions. Among 570 peptide bonds in Hb, selective cleavage was observed at only eleven sites, each occurring at Asp−X peptide bonds located in the positive patches on the protein surface. The molecular origins of the observed Asp−X selectivity were rationalized by means of molecular docking, DFT‐based binding, and mechanistic studies on model peptides. The proposed mechanism of hydrolysis involves coordination of the amide oxygen to Zr IV followed by a direct nucleophilic attack of the side chain carboxylate group on the C‐terminal amide carbon atom with formation of a cyclic anhydride, which is further hydrolyzed to give the reaction products. The activation energy for the cleavage of the structurally related Glu−X sequence compared to Asp−X was calculated to be higher by 1.4 kcal mol −1, which corresponds to a difference of about one order of magnitude in the rates of hydrolysis. The higher activation energy is attributed to the higher strain present in the six‐membered ring of glutaric anhydride (Glu−X), as compared to the five‐membered ring of the succinic anhydride (Asp−X) intermediate. Similarly, the cleavage at X−Asp and X−Glu bonds are predicted to be kinetically less likely as the corresponding activation energies were 6 kcal mol −1 higher, explaining the experimentally observed selectivity. The synergy between the negatively charged polyoxometalate cluster, which binds at positive patches on protein surfaces, and selective activation of Asp−X peptide bonds located in these regions by Zr IV ions, results in a novel class of artificial proteases with aspartate‐directed reactivity, which is very rare among naturally occurring proteases. Abstract : Artificial proteases : Strictly site‐selective hydrolysis of a multi‐subunit globular protein, hemoglobin (Hb) from bovine blood, by a range of Zr IV ‐substituted polyoxometalates (Zr‐POM) is reported. The molecular origins of the observed Asp−X selectivity were rationalized by means of molecular docking, DFT‐based binding, and mechanistic studies on model peptides.